THE CONTEMPORARY INTERPRETATION OF THE ETIQUETTE OF REQUESTING PERMISSION IN FAKHRUDDIN ALI SAFIY’S “ODOB UL-AS’HOB” (TAMADDUN NURI JURNALI, 2025)
In this article, the etiquette of seeking permission based on Faxruddin Ali Safiy’s work “Adab ul-As’hob” is analyzed within the context of Islamic ethical systems and modern social culture. The study explores the historical, religious, moral, and philosophical foundations of seeking permission, highlighting its relevance in today’s society.